2020
DOI: 10.3390/ijms21031099
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Atg7 Induces Nuclear-LC3 Dependent Apoptosis and Augments Chemotherapy in Colorectal Cancer Cells

Abstract: Autophagy is a catabolic process that enables cells to degrade obsolete content and refuel energy depots. In colorectal cancer (CRC) autophagy has been shown to promote tumorigenesis through energy delivery in the condition of uncontrolled proliferation. With this study, we aimed at evaluating whether autophagy sustains CRC cell viability and if it impacts therapy resistance. Initially, a colorectal cancer tissue micro array, containing mucosa (n = 10), adenoma (n = 18) and adenocarcinoma (n = 49) spots, was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Further, the nuclear pool of LC3 has a specific function in priming starved cells for autophagy induction underpinning our finding that autophagy induction might be part of the enhanced cell killing upon Keap1 inhibition. In line, recent studies showed nuclear LC3 accumulation to be associated with cell death in colorectal cancer cells and human oocytes 41,42 . Regarding altered levels of Rad50, cleavage PARP1, pATM S1981, Ku80 and MRE11, we believe that the detected changes occur through a cellular attempt to compensate between NHEJ and HR repair processes.…”
Section: Discussionsupporting
confidence: 67%
“…Further, the nuclear pool of LC3 has a specific function in priming starved cells for autophagy induction underpinning our finding that autophagy induction might be part of the enhanced cell killing upon Keap1 inhibition. In line, recent studies showed nuclear LC3 accumulation to be associated with cell death in colorectal cancer cells and human oocytes 41,42 . Regarding altered levels of Rad50, cleavage PARP1, pATM S1981, Ku80 and MRE11, we believe that the detected changes occur through a cellular attempt to compensate between NHEJ and HR repair processes.…”
Section: Discussionsupporting
confidence: 67%
“…Given the fact that nucleolar impairment by multiple triggers similarly induced expression of autophagy related factors, our findings suggest a novel nucleolar stress response that might globally be activated as compensatory mechanism to inhibit or delay apoptosis in the cells. Note that enhanced levels of ATG7, for instance, have been reported in diverse cancer types and were shown to promote cancer survival and resistance to chemotherapy, whereas a downregulation could counteract cancer development, progression and resistance [ 53 , 54 ]. Whether ATG7 upregulation indeed represents a cause for diverse diseases associated with nucleolar stress needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Since blocking the autophagy process by pharmacological or genetic (e.g., knockdown of Beclin 1 , ATG, or ULK1/2 genes) modulation improves tumor sensitivity chemotherapy ( Xiao et al., 2021 ) or photodynamic therapy ( Martins et al., 2021 ), there has been considerable interest in developing new clinically relevant autophagy inhibitors. For instance, the disruption of up-regulated ATG7 induces tumor cell death by triggering apoptosis, which is strictly dependent on nuclear LC3B ( Scherr et al., 2020 ). On the other hand, with inhibition of VPS34 signal transduction (siRNA therapy), tumor cell proliferation was significantly suppressed after combination chemotherapy ( Zhu et al., 2015 ).…”
Section: Modulation Of Autophagy As Cancer Therapymentioning
confidence: 99%